Advanced architectures in the design of responsive polymers for cancer nanomedicine. Issue 24 (31st January 2018) - Wagner, Angela M.; Spencer, David S.; Peppas, Nicholas A.
ABSTRACT: In recent decades, nanoparticles have shown significant promise as an oncology treatment modality. Responsive polymers represent a promising class of nanoparticles that can trigger delivery through the exploitation of a specific stimuli. Response to a stimulus is one of the most basic processes found in living systems. As such, the desire to engineer dynamic and functional materials is becoming more prevalent in an effort to achieve precise control over our environment. The combination of controlled radical polymerization and high yielding chemistry strategies provide an excellent basis for the development of the next generation of drug delivery systems. The versatility of polymer chemistries available enables the synthesis of increasingly complex architectures with enhanced delivery specificity and control over the desired properties to interface with biological systems. This tutorial review highlights recent developments in polymer‐based approaches to internally responsive nanoparticles for oncology. Presented are concise overviews of the current challenges and opportunities in cancer nanomedicine, common polymer‐based architectures, and the basis for internally triggered stimuli–response relationships commonly employed in oncology applications. Examples of the chemistry used in the design of environmentally labile nanomaterials are discussed, and we outline recent advances in creating advanced bioresponsive drug delivery architectures. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46154. Abstract :